Safety of 3 Tesla Magnetic Resonance Imaging in Patients with Sickle Cell Disease. (12th May 2021) - Justice, Olivia; Jordan, Lori C.; Lee, Chelsea A.; Patel, Niral J.; Waddle, Spencer; Pruthi, Sumit; Davis, L. Taylor; Kassim, Adetola A.; Donahue, Manus J.
Abstract : Sickle cell disease (SCD) is a well-characterized hemoglobinopathy affecting more than 20 million individuals worldwide and carries an increased risk of cerebral vasculopathy, cerebral infarct, and stroke. As mechanisms of cerebral infarction in SCD are partly attributable to microvascular vaso-occlusive crises, manifesting as altered cerebral blood flow and associated impaired oxygen delivery, magnetic resonance imaging (MRI) methods that can quickly provide a comprehensive perspective on structural and functional disease status, without exogenous contrast administration or ionizing radiation, have emerged as crucial clinical tools for surveillance. However, early ex vivo MRI work in suspended erythrocytes containing hemoglobin S at 0.35 Tesla (T) suggested that sickled erythrocytes can orient preferentially in the presence of an external magnetic field, and as such, it was suggested that MRI exams in sickle cell hemoglobinopathy could induce vaso-occlusion. While this observation has generally not impacted clinical imaging in individuals with SCD, it has led to resistance for some sickle cell studies within the engineering community among some imaging scientists as this early observation has never been rigorously shown to be unconcerning. Here, we performed MRI at the clinical field strength of 3 T in 172 patients with SCD, which included standard anatomical and angiographic assessments together with gold standard diffusion-weighted imaging (DWI; spatial resolution = 1.8 × 1.8 × 4 mm; b -value = 1000 s/mm 2 ) for acute infarct assessment (performed approximately 20 min after patient introduction to the field isocenter). The presence of vasculopathy, as well as chronic and acute infarcts, was evaluated by two independent board-certified radiologists using standard clinical criteria. In these patients (52.3% female; mean age = 19.6 years; age range = 6–44 years), hematocrit (mean = 25.8%; range = 15–36%), hemoglobin phenotype (87.8% HbSS variant), presence of silent infarct (44.2%), and overt chronic infarct (13.4%) were consistent with a typical SCD population; however, no participants exhibited evidence of acute infarction. These findings are consistent with 3 T MRI not inducing acute infarction or vaso-occlusion in individuals with SCD and suggest that earlier low-field ex vivo work of erythrocytes in suspension is not a sufficient cause to discourage MRI scans in patients with SCD.